The comparison of soil contaminated by landfill leachate & industrial wastewater - Siti Hajar Fattyne , Zulkfli (2012)
Soil contaminated caused by leachate and industrial wastewater is extremely dangerous to human life and also gives negative impact on the groundwater and the soil structure. This project aims to study the parameters of soil contaminated by Jeachate and industrial wastewater. Besides that, to compare the quality standards of the dissolved soil with leachate and industrial wastewater with Standard Environmental Quality Act 1974. The sample for the leachate and wastewater was taken at the landfill Jerangau, Jabor and mechanic workshop near Gambang, Kuantan. Then, the uncontaminated soil sample was taken near the Kolej Kediaman 2, KK2, UMP. Non-contaminated soil is mixed with leachate and industrial wastewater experiment was conducted in soil and geotechnical laboratory also in environmental laboratory to study the parameters that have been contaminated soil. The test that had been conducted during the laboratory are Atterberg limits test, moisture content, proctor test, pH test, suspended solid test, COD and ROD test. From the experiment showed that the result for contaminated soil increase for the plastic index, pH value, suspended solid, COD and BOD compared to the uncontaminated soil. Then for the permeability and proctor test, the result showed that contaminated soil decrease compared to the uncontaminated soil.